2011
DOI: 10.1039/c1an15535k
|View full text |Cite
|
Sign up to set email alerts
|

Localized surface plasmon resonance interfaces coated with poly[3-(pyrrolyl)carboxylic acid] for histidine-tagged peptide sensing

Abstract: The paper reports on a novel localized surface plasmon resonance (LSPR) substrate architecture for the immobilization and detection of histidine-tagged peptides. The LSPR interface consists of an ITO (indium tin oxide) substrate coated with gold nanostructures. The latter are obtained by thermal deposition of a thin (2 nm thick) gold film followed by post-annealing at 500 °C. The LSPR interface was coated with poly[3-(pyrrolyl)carboxylic acid] thin films using electrochemical means. The ability of the LSPR int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…[16][17][18][19] One of the most versatile and powerful methods to control the molecular orientation of immobilized biomolecules onto surfaces is based on metal-chelating agents and their specic affinity for proteins and peptides containing histidine residues. 16,[20][21][22] This paper therefore reports on the preparation of BDD nanowires for histidine-tagged peptides capture and detection using electrochemical impedance spectroscopy (EIS). We have recently shown that BDD NWs modied with nickel nanoparticles allow site-specic orientation of His-tagged peptides.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] One of the most versatile and powerful methods to control the molecular orientation of immobilized biomolecules onto surfaces is based on metal-chelating agents and their specic affinity for proteins and peptides containing histidine residues. 16,[20][21][22] This paper therefore reports on the preparation of BDD nanowires for histidine-tagged peptides capture and detection using electrochemical impedance spectroscopy (EIS). We have recently shown that BDD NWs modied with nickel nanoparticles allow site-specic orientation of His-tagged peptides.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO NWs are prepared by means of vapor transport process, in which the source material is vaporized and transported by a gas carrier towards the substrates where it condenses [24]. The experimental setup consists of a furnace capable to reach temperatures needed for oxide evaporation, a vacuum-sealed alumina tube connected to a vacuum pump, an automated valve, and a mass flow meter to control pressure and carrier flux.…”
Section: Methodsmentioning
confidence: 99%
“…A convenient way to modify the surface of conducting materials such as LSPR nanostructures is through electrodeposition of thin oligomeric or polymeric films from solution monomers. 91,92 Varying parameters such as the monomer concentration, deposition potential and deposition time allow controlling the thickness of the deposited polymer, a crucial parameter for LSPR sensing. Thin films of polyaniline (100 nm) were electrochemically deposited on gold nanostructures on a conducting ITO interface and were used to modulate the LSPR signal upon polyaniline switching from its reduced to its oxidized state.…”
Section: Polymer Films 421 Conducting Polymer Filmsmentioning
confidence: 99%
“…13). 91 The terminal carboxylic acid groups on the LSPR interface chelating of Cu 2+ ions and subsequent immobilization of histidine-tagged proteins in a controlled orientation. 9 4.2.2.…”
Section: Polymer Films 421 Conducting Polymer Filmsmentioning
confidence: 99%